Are homeschooled adolescents less likely to use alcohol, tobacco, and other drugs?. (1st October 2015) - Vaughn, Michael G.; Salas-Wright, Christopher P.; Kremer, Kristen P.; Maynard, Brandy R.; Roberts, Greg; Vaughn, Sharon
Highlights: Homeschool adolescents were more likely to disapprove of alcohol/marijuana use. Homeschool adolescents were less likely to use tobacco, alcohol, and cannabis. Homeschool adolescents were less likely to have a diagnosed alcohol use disorder. Homeschool adolescents had less access to illicit drugs than non-homeschool peers. Abstract: Background: Nearly two million school-aged children in US are currently homeschooled. This study seeks to examine homeschooled adolescents' attitudes toward, access to, and use of alcohol, tobacco, and other drugs (ATOD) compared to their non-homeschooled peers. Methods: The study uses data between 2002 and 2013 from the National Survey on Drug Use and Health (NSDUH) for school-attending respondents aged 12–17 ( n  = 200, 824). Participants were questioned regarding peer use of licit and illicit substances, ease of accessing illicit substances, and past 12-month substance use. Survey adjusted binary logistic regression analyses were systematically executed to compare non-homeschooled adolescents with homeschooled adolescents with respect to views toward, access to, and use of substances. Results: Findings indicate that homeschooled adolescents were significantly more likely to strongly disapprove of their peers drinking (AOR = 1.23) and trying (AOR = 1.47) and routinely using (AOR = 1.59) marijuana. Homeschooled adolescents were significantly less likely to report using tobacco (AOR = 0.76), alcohol (AOR = 0.50), cannabis (AOR = 0.56) and other illicit drugs and to be diagnosed with an alcohol (AOR = 0.65) or marijuana (AOR = 0.60) use disorder. Finally, homeschooled adolescents were also less likely to report easier access to illicit drugs and to be approached by someone trying to sell drugs compared to non-homeschooled peers. Conclusions: Homeschooled adolescents' views, access, use and abuse of ATOD are uniquely different from those of non-homeschooled adolescents. Findings point to the need to more extensively examine the underlying mechanisms that may account for these differences.